In silico study of the influences of cooling rates on the phase transition of water inside the carbon nanotube under different ambient pressures - Lam, Vi Toan; Nguyen, Hoang Giang; Nguyen, Van Hoa; Nguyen, Minh Phi; Tran, Thi Thu Hanh (Communications in Physics, 2022)
By using MD simulation method, this study shows the influences of cooling rates on the solidifying temperature of water inside a single-wall-carbon-nanotube under different ambient pressures when cooling the systems from 300 K down to 200 K. Our results showed that the more rapid cooling rate of the systems creates more disruptive and dramatic phase transitions. Moreover, we also found that the lower of pressures correlates to the more dramatic phase transitions of water, regardless of cooling rate. This study generally provides more insight into water behavior in the SWCNT with variations in ambient conditions.